2012
DOI: 10.1073/pnas.1205707109
|View full text |Cite
|
Sign up to set email alerts
|

Total kinetic analysis reveals how combinatorial methylation patterns are established on lysines 27 and 36 of histone H3

Abstract: We have developed a targeted method to quantify all combinations of methylation on an H3 peptide containing lysines 27 and 36 (H3K27-K36). By using stable isotopes that separately label the histone backbone and its methylations, we tracked the rates of methylation and demethylation in myeloma cells expressing high vs. low levels of the methyltransferase MMSET/WHSC1/NSD2. Following quantification of 99 labeled H3K27-K36 methylation states across time, a kinetic model converged to yield 44 effective rate constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
160
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(177 citation statements)
references
References 35 publications
17
160
0
Order By: Relevance
“…We found that K27me3 rarely co-exist with K36me1/me2 (except for the H3⌬G12 tail). This result conforms to previous studies suggesting antagonism between high methylation states of H3K27 and H3K36 (23,24). K14ac and K23ac were found to be mutually exclusive by interplay analysis, in agreement with a previous report (15).…”
Section: Histones H2b and H3 Undergo Proteolytic Processing In A Hepasupporting
confidence: 83%
“…We found that K27me3 rarely co-exist with K36me1/me2 (except for the H3⌬G12 tail). This result conforms to previous studies suggesting antagonism between high methylation states of H3K27 and H3K36 (23,24). K14ac and K23ac were found to be mutually exclusive by interplay analysis, in agreement with a previous report (15).…”
Section: Histones H2b and H3 Undergo Proteolytic Processing In A Hepasupporting
confidence: 83%
“…By contrast, combinatorial modifications define the co-existence of any number of modifications that is greater than two on proteolytic peptides or intact proteins. For example, we have identified 15 combinatorial modifications of H3K27 and H3K36 methylation in our previous Bottom-Up study of peptides from H3.1 and H3.2 containing residues 27 to 40, without knowing the modification status beyond this region (29). In this study, we were able to achieve a clean isolation of each Methyl-Eq by virtue of the 0.6 Th isolation window, which ensured the MS 2 spectra were derived from a single isolated precursor.…”
Section: Mmset-highmentioning
confidence: 88%
“…These results underscore the importance of EZH2-mediated H3K27 trimethylation in drug sensitivity in MM cells. Finally, we asked whether MMSET exerted drug resistance via the same mechanisms because MMSET overexpression downregulates H3K27me3 and has been identified as a marker of worse prognosis in MM patients (7,8). To this end, we overexpressed MMSET in t(4;14)-negative RPMI8226 cells and knocked it down in t(4;14)-positive KMS-11 cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the SET domain-containing histone methyltransferase MMSET/KMT3G is overexpressed in an aggressive form of MM carrying t (4;14), leading to altered chromatin states by inducing an increase in H3K36me2 and decrease in H3K27me3 (7,8). The oncogenic function of MMSET is closely associated with its catalytic activity in MM (9)(10)(11), making it amenable to therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%